PENDAMPINGAN PEMANFAATAN DAUN TAPAK DARA (Catharanthus roseus L. ) SEBAGAI FACE MIST TABIR SURYA DI PONDOK PESANTREN ADNAN AL-CHARISH - Al-bari, Akhmad; Qoriati, Yani; Februyani, Nawafila (Universitas Mataram, 2025)
Community service activity aimed to enhance the knowledge and skills of the female students at Pondok Pesantren Adnan Al-Charish in utilizing Madagascar periwinkle (Catharanthus roseus L.) as a raw material for producing a natural, locally sourced sunscreen in the form of a face mist. Catharanthus roseus contains various secondary metabolites such as alkaloids, terpenoids, phenols, tannins, saponins, quinines, and sterols, with vincristine and vinblastine as the main compounds known for their antioxidant, antimitotic, and potential ultraviolet (UV) protection activities. The method employed was Participatory Action Research (PAR), consisting of observation, survey, preparation, training, and evaluation stages. The training involved 30 female students who directly practiced making face mist from C. roseus leaf extract using the infusion method, combined with PVP and glycerin, followed by pH testing and product packaging. Evaluation results showed a significant improvement in participants’ knowledge, with post-test results indicating 89.1% in the high category compared to the pre-test, which was dominated by the low category. This program not only improved participants’ understanding and practical skills but also raised awareness about utilizing local natural resources to develop functional products with beneficial and economic potential.